Effect of nitrobenzene on growth and yield of boro rice - Chowdhury, B; Howlader, MHK; Hossain, MK; Sikder, MC; Hasan, MM (Progressive Agriculture, 2019)
The present experiment was conducted at the research field of Patuakhali Science and Technology University (PSTU), Patuakhali during the period from December 2013 to March 2014 to evaluate the effect of Nitrobenzene as plant growth regulators on growth and yield parameters of Boro Rice. It also observed the comparative growth and yield performance of foliar application Nitrobenzene ( 0, 1.0, 3.0 and 5.0 ml L–1). Data were collected on Plant height; number of leaves plant–1; number of total, effective and non–effective tillers hill–1; leaf area (LA); leaf area index (LAI); total dry matter (TDM); Crop and relative growth rate (CGR and RGR); and Yield and yield contributing characters such as length of root; length of panicle; number of total, sterile and non–sterile spikelets panicle–1; 1000–grain weight; grain, straw and biological yield and harvest index (HI). The experiment was laid out in a completely randomized block design (RCBD) with three replications. The collected data were analyzed statistically and means were adjudged by DMRT at 5% level of probability. The treatments Nitrobenzene @ 3.0 ml L–1 as foliar application gave the highest performance in respect of plant height (90.39 cm), LAI (3.514), TDM (19.17 g plant–1), effective tiller (20.33 hill–1), total tillers (22.73 hill–1), panicle length (26.01 cm),non sterile spikelets (134.70 panicle–1), total spikelets (155.80 panicle–1), 1000–grain weight (28.21 g), grain yield (5.86 t ha–1), straw yield (8.44 t ha–1), biological yield (14.29 t ha–1) and HI (41.00%) of boro rice. Progressive Agriculture 29 (4): 304-312, 2018